Thirty-three vascular residency programs among 13 countries joining forces to improve surgical education in times of COVID-19: A survey-based assessment. (February 2022) - Fabiani, Mario Alejandro; Gonzalez-Urquijo, Mauricio; Cassagne, Gabriela; Dominguez, Angeles; Hinojosa-Gonzalez, David Eugenio; Lozano-Balderas, Gerardo; Cisneros Tinoco, Miguel Ángel; Escotto Sanchez, Ignacio; Esperón Percovich, Alejandro; Vegas, Diego Herrera; Mariné Massa, Leopoldo; Mertens, Renato A; et al.
Background: Academic interaction with mentors has almost become minimal due to the current pandemic of COVID-19. The objective of this study is to introduce how a group of vascular surgery residencies joined forces to improve surgical education in times of COVID-19. Methods: On May 2020, a group of Hispanic American vascular residency programs created webinar sessions of arterial and venous clinical cases among vascular residents across Latin America and Europe. Participants were surveyed via email. Questions were about the perceived quality and utility of the webinars; answers were stratified into negative (disagree), neutral, and positive (agree). Results: There have been 60 sessions and 118 clinical cases presented. The survey was answered by 106 participants, 82 males (78.8%) and 24 women (23.0%). Fifty-four (51.9%) were board-certified vascular surgeons, 49 (47.1%) vascular surgery residents, and 2 (1.9%) general surgery residents. Mean age of the participants was 41.5 years (range: 25–74 years). Mean years of vascular surgery practice or experience were 11.2 years (range: 0–45 years). The residency programs involved in this project were from 13 different countries. Most answers received were positive for both perceived quality and utility of the webinars. Conclusion: Globalization and technology provide an opportunity for international education, with the goal of building well-rounded and academic vascular surgeons. This group is just the beginning of a large collaborative group among Hispanic American countries, hoping that more residency programs will join, with the aim of breaking borders in the education of vascular surgery.